2005
DOI: 10.1213/01.ane.0000166952.12290.45
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Plasma Concentration of Ketamine That Enhances Epidural Bupivacaine-and-Morphine-Induced Analgesia

Abstract: N-methyl-D-aspartate (NMDA) receptor antagonists enhance opioid-induced analgesia. The plasma concentration of ketamine, an NMDA receptor antagonist that enhances epidural morphine-and-bupivacaine-induced analgesia, is not known. We examined 24 patients with lung carcinoma or metastatic lung tumor who underwent video-assisted thoracic surgery in a placebo-controlled, double-blind manner 4 h after emergence from anesthesia. The morphine + ketamine group (n = 8) and morphine + placebo group (n = 8) received 5 mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Whereas anaesthesia-inducing plasma concentrations of ketamine in humans have been reported to be above 1 g/ml (Malinovsky et al, 1996;Weber et al, 2004), adequate pain relief-associated plasma levels of this anesthetics are several fold lower, situating around 20 ng/ml (Suzuki et al, 2005). Although it is ethically impossible to determine blood-brain distribution coefficient of ketamine in humans, based on experimental studies of ketamine pharmacokinetics (Edwards et al, 2002), it is thus strongly possible, as discussed above, that plasma concentrations of 20 ng/ml of ketamine result in several fold higher brain concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…Whereas anaesthesia-inducing plasma concentrations of ketamine in humans have been reported to be above 1 g/ml (Malinovsky et al, 1996;Weber et al, 2004), adequate pain relief-associated plasma levels of this anesthetics are several fold lower, situating around 20 ng/ml (Suzuki et al, 2005). Although it is ethically impossible to determine blood-brain distribution coefficient of ketamine in humans, based on experimental studies of ketamine pharmacokinetics (Edwards et al, 2002), it is thus strongly possible, as discussed above, that plasma concentrations of 20 ng/ml of ketamine result in several fold higher brain concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…The majority of studies characterized the NMDA receptor antagonists as enhancing or having no effect on analgesia, whereas a minority demonstrated attenuation of acute morphine analgesia (88)(89)(90)(91)(92)(93). One challenge in this area is the absence of consistent results identifying which opioids exhibit NMDA receptor antagonist-enhanced antinociception.…”
Section: Nmda Receptor Contributions To Opioid Tolerancementioning
confidence: 99%
“…Indeed, clinical studies have demonstrated that NMDAR antagonists do not alter opioid tolerance in humans (Compton et al, 2008;Galer et al, 2005). Part of the confusion may stem from the fact that NMDAR antagonists like ketamine have been demonstrated to have an additive effect on opioid analgesia (Suzuki et al, 2005;Wadhwa et al, 2001;Weinbroum et al, 2002;Wiesenfeld-Hallin, 1998) which may have an effect on the reflex-based measures of antinociception in animal studies (Carlezon et al, 2000). In order to determine if attenuated tolerance is an artifact of reflex-based measures, we investigated the effects of the NMDAR antagonist MK-801 on morphine tolerance in a non-reflex based operant orofacial thermal pain assay.…”
mentioning
confidence: 99%